2014
DOI: 10.1073/pnas.1321621111
|View full text |Cite
|
Sign up to set email alerts
|

Structures of the PutA peripheral membrane flavoenzyme reveal a dynamic substrate-channeling tunnel and the quinone-binding site

Abstract: Proline utilization A (PutA) proteins are bifunctional peripheral membrane flavoenzymes that catalyze the oxidation of L-proline to L-glutamate by the sequential activities of proline dehydrogenase and aldehyde dehydrogenase domains. Located at the inner membrane of Gram-negative bacteria, PutAs play a major role in energy metabolism by coupling the oxidation of proline imported from the environment to the reduction of membrane-associated quinones. Here, we report seven crystal structures of the 1,004-residue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
121
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(131 citation statements)
references
References 31 publications
10
121
0
Order By: Relevance
“…The observed lag time is greater than that observed for PutA. The lag times reported for PutA enzymes thus far range from no apparent lag to 23 s for E. coli PutA (8,9,11). The longer lag time of the TtPRODH- (50).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…The observed lag time is greater than that observed for PutA. The lag times reported for PutA enzymes thus far range from no apparent lag to 23 s for E. coli PutA (8,9,11). The longer lag time of the TtPRODH- (50).…”
Section: Discussionmentioning
confidence: 72%
“…Crystal structures of PutA enzymes from Bradyrhizobium japonicum (8) and Geobacter sulfurreducens (9) revealed that the two active sites are separated by a linear distance of 40 -50 Å and connected by a curved tunnel that traverses ϳ70 Å. Kinetic data for these enzymes are consistent with a substrate channeling mechanism (8,9).…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…This method requires prior knowledge of a particular gene in the pathogenesis of the disorder. The gene and surrounding DNA is analyzed through case-control association studies for comparison among people with and without disease to figure out alterations specific to people having the disease phenotype (Singh et al, 2014). Similarly, allele specific methods and direct sequencing of entire candidate region in both cases and controls are also exploited.…”
Section: Genetic and Computational Approaches To Seek Disease Genesmentioning
confidence: 99%